Sistem Informasi Manajemen Aset Politeknik Manufaktur Negeri Bangka Belitung - Riki Afriansyah (Fakultas Teknologi Informasi - Universitas Advent Indonesia, 2022)
The design of an asset management information system for the Bangka Belitung State Manufacturing Polytechnic uses the prototype method. By using this prototype method, the BMN asset management staff is directly involved from the beginning to the end so that the information system built is in accordance with the wishes and needs of system users. at the prototype development stage using the UML model because the system built applies the object oriented concept and functional testing of asset information systems using the blackbox testing method. The integration of the QR Code in the asset management information system makes it easier to present asset information. The results of the measurement system in terms of time are obtained that by using an asset information system, the management and presentation of information is faster than using conventional methods. Asset management staff can easily filter data as needed.